Local knowledge management and innovation spillover - Dias, Á.; Gomes, M.; Pereira, L.; Lopes da Costa, R. (International Journal of Service Science, Management, Engineering, and Technology, 2022)
Tourism lifestyle entrepreneurs play an essential role in the innovation and competitiveness of tourist destinations. However, existing knowledge about the determinants of the innovation they generate is far from being fully exploited. There is still little knowledge about the innovation spillover effect, which is a determining factor for the destination's competitiveness. One of the key factors for innovation results from local knowledge management and the ability of tourism lifestyle entrepreneurs to turn this knowledge into innovation. To test the role of knowledge management in innovation and spillover, a survey was conducted on a sample of 115 tourism lifestyle entrepreneurs, with the hypotheses tested using structural equations. The results reveal that place attachment and knowledge acquisition have a direct effect on knowledge assimilation and community-centered strategy. Furthermore, it was also found that community-centered strategy and knowledge assimilation play a mediating role between place attachment and innovation capacity.